Alp rose stem cells as cosmetic creams ingredient: Expected and established creams effects on the skin - Filipović Mila; Lukić Milica; Savić Snežana; Vuleta Gordana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2018)
In the cosmetic industry, a frequent anti-aging approach is the protection of cells responsible for the continuous skin renewal and the maintenance of its barrier function - epidermal stem cells, using the secondary metabolites and epigenetic factors of the plant stem cells. Alp rose stem cells (ARSC) extract in liposomes is used as a cosmetic active ingredient in the cosmetic products for the skin care and its protection. According to the manufacturer, this cosmetic active ingredient possess the ability to increase the vitality of epidermal stem cells, protects them against the negative external influences, affects the regeneration of epidermal cells, improves the skin barrier function and has certain anti-aging effects. However, in order for these effects to be observed in in vivo conditions and for ARSC epigenetic factors and secondary metabolites to reach their target places, liposomes in the cosmetic products should remain intact and unchanged. Therefore, according to the EU regulations on the cosmetic products (Regulations 1223/2009 and 655/2013), cosmetic products with plant (alp rose) stem cells can not be attributed to the effects of the containing cosmetic ingredients, and any claims about the each product efficacy has to be supported by the data obtained on the human volunteers.